Role of salivary protease activity in adherence of gram-negative bacilli to mammalian buccal epithelial cells in vivo. - Woods, D E (1981)
Serious illness is accompanied by markedly increased susceptibility to colonization of the respiratory tract by gram-negative bacilli and an increase in the number of such organisms which adhere to regional epithelial cells during incubation in vitro. Trypsinization of cells from normal subjects causes a similar increase in bacillary adherence. We studied bacillary adherence to buccal cells in vitro, protease activity of upper respiratory secretions with a fibrin plate technique, and the amount of fibronectin on the surface of buccal cells with a direct radioimmunobinding assay. Among 10 patients seriously ill with acute respiratory failure bacillary adherence to buccal cells and protease activity in secretions were increased compared with controls and cell-surface fibronectin was decreased; all patients were colonized in vivo with gram-negative bacilli. These changes were persistent and 80% of the patients died. Serial determinations were made in eight patients undergoing coronary artery bypass surgery. Following surgery, protease activity and bacillary adherence increased and cell-surface fibronectin decreased; 38% of coronary artery bypass patients became colonized. In these uncomplicated patients the changes observed were transient, largely returning to normal by the third postoperative day. Increased protease activity of secretions and alterations in epithelial cell surfaces as reflected by loss of buccal cell-surface fibronectin occur swiftly after major illness and appear to underlie enhanced cell adherence of bacilli and colonization of the upper respiratory tract. These findings suggest new approaches to the prevention of nosocomial pneumonia.